The relevance of improving the maintenance system of the railway track based on the efficient use of labor resources - Lesov, Kuvondik Saginovich; Isroilov, Otabek Batirovich (Science and Education, 2023)
The main purpose of the article is to explain the relevance of improving the maintenance system of the railway track based on the efficient use of labor resources. The maintenance of the track is occupied by a large team of track workers, and the solution of these tasks is largely determined by the extent to which, with the available means of mechanization, the contingent of track workers in terms of composition and qualifications corresponds to what is required to perform the necessary types and volumes of work on the current maintenance of the track.